Synthesis and bacteriostatic activities of bis(Thiourea) derivatives with variable Chain Length - Ainaa Nadiah, Abd Halim; Ngaini, Zainab (Hindawi Publishing Corporation, 2016)
A series of 1,4-bis(decoxyphenyl)carbamothioyl-Terephthalamide derivatives was successfully synthesised by reaction of benzene- 1,4-dicarbonyl isothiocyanate intermediates with long alkyl chain. The alkylation was performed via Williamson etherification of 4-Acetamidophenol with bromoalkanes.The synthesised bis(thiourea) derivatives differed in the chain length, CnH2n+1, where n = 10, 12, and 14. The structures of all compounds were characterised by elemental CHN analysis, IR, 1H, and 13C NMR spectroscopies. Bacteriostatic activities of bis(thiourea derivatives which consisted of two folds of N-H, C=O, and C=S and long alkyl chain substituents were carried out against Gram-negative bacteria (Escherichia coli, ATCC 25922) via turbidimetric kinetic method. Bis(thiourea) derivatives with n = 10 and n = 12 displayed excellent activity against E. coli with MIC of 135 μg/mL and 145 μg/mL, respectively, while bis(thiourea) derivatives with n = 14 acted as cutoff point with no antibacterial properties. Similar trend was observed in binding affinity to the active site of enoyl ACP reductase (FabI), which demonstrated binding free energy of -5.3 Kcal/mol and -4.9 and -4.8 Kcal/mol, respectively.